Beyond The Classroom: Engineering a Greener Future - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
A poster promoting the presentation "Engineering a Greener Future, One Change at a Time" hosted by Dr. Jennifer Anthony, Associate Professor of Chemical Engineering, at Kansas State University on February 5, 2015 at 7 PM.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; Engineering; Posters